แนวทางการพัฒนาการมีส่วนร่วมของชุมชนท่าวังผาในการจัดการท่องเที่ยวเชิงนิเวศอำเภอท่าวังผา จังหวัดน่าน - สุดศิริ หอมกลิ่น (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This research aimed to study the community participation for developing eco-tourism management of Thawangpha district, Nan province. Data was collected by questionnaire from 200 local people and 200 tourists as well as by interviewing 44 persons from government agencies, private sectors, and leaders of communities that were related to the eco-tourism of Thawangpha district. Content analysis was used in qualitative analysis and the amount of percentage (%), mean (X¯) and standard deviations (S.D.) were used in quantity analysis. The differences of demographic profile of local people were compared by using independent samples tests (t-test independent) and Analysis of Variance (One–way ANOVA). If the results were significantly different at the level .05, the Scheffe method would then be employed. Furthermore, this research used focus group method to acquire the guideline for encouraging local community to participate in eco-tourism management. The results were as follows: 1. Factors affecting readiness to be ecotourism of Thawangpha district, Nan province were found to be at high level including Local souvenirs (X¯ = 2.69), facilities (X¯ = 2.52) and accommodation (X¯ = 2.52). 2. Guidelines for eco-tourism needed to be developed was to encourage local people to manage eco-tourism (X¯ = 2.99) and investment in eco-tourism development (X¯ = 2.97). 3. Level of community participation in eco-tourism were found to be in low level regarding decision making (X¯ = 2.37), planning (X¯ = 2.17) and evaluation(X¯ = 2.32) at low level. However, they participated in implementation (X¯ = 2.65) at high level. 4. Comparison of participation level of local people classified by gender was found to demonstrate difference at statistical .05 level in decision making level. 5. Comparison of participation level of local people classified by age groups, education level, occupations and monthly income were found to be no significant differences. 6. Guidelines for encouraging community to participate in eco-tourism management including: 1) sharing ideas and discussion on eco-tourism management among all tourism stakeholders, 2) creating eco-tourism plans, 3) encouraging projects for developing potential of local people to manage eco-tourism and 4) evaluating eco-tourism development programs by meeting and discussing among all stakeholders.